Strategies and mechanisms targeting Enterococcus faecalis biofilms associated with endodontic infections: a comprehensive review - Yang, Shipeng; Meng, Xiuping; Zhen, Yuqi; Baima, Quzhen; Wang, Yu; Jiang, Xinmiao; Xu, Zhibo (Frontiers in Cellular and Infection Microbiology, 2024)
Enterococcus faecalis is one of the main microorganisms that infects root canals, ranking among the most prevalent microorganisms associated with endodontic treatment failure. Given its pervasive presence in persistent endodontic infections, the successful elimination of Enterococcus faecalis is crucial for effective endodontic treatment and retreatment. Furthermore, Enterococcus faecalis can form biofilms - defense structures that microbes use to fight environmental threats. These biofilms confer resistance against host immune system attacks and antibiotic interventions. Consequently, the presence of biofilms poses a significant challenge in the complete eradication of Enterococcus faecalis and its associated disease. In response, numerous scholars have discovered promising outcomes in addressing Enterococcus faecalis biofilms within root canals and undertaken endeavors to explore more efficacious approaches in combating these biofilms. This study provides a comprehensive review of strategies and mechanisms for the removal of Enterococcus faecalis biofilms.